Street Voice: Can Citizens' Juries help tackle urban sustainability challenges? - Chisholm, A; Carpenter, J; Pope, C; Howard, D; Weavers, R (Elsevier, 2023)
Urban planning practice faces a crisis of legitimacy, with a mistrust of democratic institutions and a scepticism in participation processes. Civic leaders are called on to engage residents constructively in challenges of urban sustainability. Through the deliberative democratic process of Citizens' Juries, a small representative group of randomly selected citizens come together to reach a collective decision on a policy issue through informed deliberation. This paper presents findings from a Citizens' Jury organised in Oxford, UK. “Street Voice” aimed to address a critical question facing cities in relation to transport, health and climate: “How can people travel where they need to in the city, in a way that's good for health and the climate?” The research facilitated deliberation between citizens on this key area related to urban sustainability, generated policy solutions for consideration by local government, and evaluated Citizens' Juries to explore a highly contentious local issue that crystallises the dilemmas and trade-offs that the decarbonisation agenda presents. Street Voice demonstrated how the a Citizens' Jury can contribute to bringing together disparate views and voices around urban sustainability, alongside other forms of decision-making in the urban arena, to bring democracy closer to citizens in critical arenas such as decarbonisation.